Perkembangan Sosial Emosional Anak Melalui Permainan Gerak dan Lagu di Taman Kanak-Kanak Permata Hati Desa Limbang Jaya I - Itryah, Itryah; Islamiyah, Sohibatul (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Social-emotional development in early childhood is an important aspect that supports children's ability to interact, manage emotions, and cooperate with the surrounding environment. This activity aims to improve children's social-emotional development through movement and song games at Permata Hati Kindergarten, Limbang Jaya Village I. The methods used are active learning, education, participatory observation and interviews, with a focus on children's involvement in motion and song games for several sessions. The results of the study showed a significant increase in children's ability to cooperate, express emotions, and communicate with peers. Children who previously tended to be passive showed progress in social interaction skills and emotional management. Motion games and songs have proven to be effective as learning methods that support children's overall social emotional development. Thus, this activity provides practical guidance for teachers in integrating movement games and songs as part of the learning process in Kindergarten.